Zadovoljstvo staršev z uporabo prilagojenih stolov za otroke z zmanjšanimi zmožnostmi gibanja - Kukovec, Tina (Rehabilitacija (Ljubljana), 2021)
Background: Children with severely impaired mobility need a well-designed chair to maintain the position of the head and trunk while sitting. In the study, we wanted to assess parental satisfaction with the use of adapted chairs for children and related services. We were also interested in which of the satisfaction items is most important for parents and what, in the opinion of the parents, the child gains by using an adapted chair. Methods: From April to July 2019, we included parents of children with impaired mobility who use an adapted chair for at least three months. To assess the level of satisfaction with the use of custom chairs for children and related services, we used the Quebec User Evaluation of Satisfaction with assistive Technology (QUEST). We also conducted a partially structured interview with parents who completed the QUEST questionnaire. We wanted to find out what their opinion is about the contribution of adapted chairs. Results: We analysed the responses of 22 parents. They estimated that they were most satisfied with the efficiency of the device and least with the weight of the chairs. In terms of services, they are most satisfied with the professionalism of the services, and least satisfied with the subsequent monitoring and support in the use and maintenance of the chairs. They rated safety and ease of use as the most important items of satisfaction. The results of four partially structured interviews showed that parents notice differences between the placement in the lap and the use of adapted chairs, the differences between a standard chair and a adapted chair, and believe that the child functions better when using such chairs. Conclusion: Parents are very happy with the use of adapted chairs for children and related services. Lower-rated satisfaction items can benefit occupational therapists working in comprehensive therapy program of children with developmental disabilities to be able to develop suggestions for improvements for adapted chairs for children in the future.
Keywords: chair; Child; Disabled Children; impaired functioning; otrok; Quebec User Evaluation of Satisfaction with assistive Technology; QUEST; rehabilitation; satisfaction; stol; zadovoljstvo; zmanjšane zmožnosti